Clinical application of ultra‐high frequency ultrasound: Discovering a new imaging frontier. Issue 6 (22nd June 2022) - Fogante, Marco; Carboni, Nicola; Argalia, Giulio
Abstract: The ultra‐high frequency ultrasound (UHFUS) is characterized by the use of probes between 30 and 100 MHz. This technology has recently been introduced in clinical practice and represents an opportunity for the diagnosis of numerous pathologies. The high spatial resolution of UHFUS, up to 30 μ in pixel size, allows to study the pathological modifications and to guide microsurgery treatments in anatomical body structures not evaluable by conventional HFUS. The aim of this work is to provide a review of the literature on the current clinical applications of UHFUS and to discuss its added role in different clinical settings. Abstract : UHFUS is a new technology with the range between 30 and 100 MHz. UHFUS frequency ultrasound represents a great opportunity for the diagnosis of numerous pathologies. UHFUS can identify the extent of the cutaneous lesion as accurately as the histopathologic examination.